Effects of Scattering of Luminescent Down-Shifting Particles Inside Ethylene-Vinyl Acetate Films on Reflection of Light - Razzaq, Shehroz; Asghar, Ali; Lou, Chaogang (Frontiers in Materials, 2021)
Silicon solar cells are suffering from a poor spectral response in short-wavelength ranges due to the loss of higher energy photons. The luminescent down-shifting (LDS) materials have the ability to convert shorter wavelength photons into longer wavelength photons and improve the performance of the solar cells. However, besides the down-shifting effects, the introduction of LDS particles into ethylene-vinyl acetate (EVA) films on the solar cells also increases surface reflection, which will negatively influence the performance of the solar cells. In this work, the influence of the size of LDS particles inside EVA films on reflection is investigated theoretically. The results showed that the reflection results from the scattering by LDS particles, which depends on the particle’s size. The total reflection caused by LDS particles can be calculated according to the size distribution of LDS particles. This work is helpful in selecting LDS particles that can be applied to solar cells.